Validating Students’ Readiness for Online Learning: Questionnaire Development and Evaluation - Mahayanti, Ni Wayan Surya; Indra Agus Eka Hariawan; Suwastini, Ni Komang Arie; Paramartha, Anak Agung Gede Yudha; Asril, Nice Maylani; Hua, Liang (Borneo Educational Journal (Borju), 2025)
The purpose of this study is to validate the students’ readiness of online learning questionnaire based on previous research, conceptualized in attitudes toward learning aspects. Six dimensions of attitudes toward learning aspects comprised of learning flexibility (LF), attitude online learning (OL), online interaction (OI), study management (SM), technology (TE), classroom learning (CL), and readiness of blended learning (RBL). 243 secondary students in a rural area in Bali participated in this study. Google form was delivered after the participants agree to join the study and filled the consent form. The data were analysed using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) to assess the hypotheses. The findings showed that a four-correlated model including attitudes toward study management, classroom learning, learning flexibility, and readiness of blended learning factors was validated by the results of EFA and CFA. Internal reliability confirmed the consistency factors, the validity provided evidence for significance relationships between them. Unlike previous study’s findings, this study discovered that attitudes toward online learning, attitudes toward technology, and attitudes toward online interaction are not essential elements of students’ readiness for online learning. This finding highlights pedagogical aspects, which turn into the essential idea in determining how prepared students are for online learning. The result can only be generalized to other areas of Indonesia through further researches